Cinacalcet Hydrochloride: a new dose schedule in the Management of Secondary Hyperparathyroidism in Indian Chronic Kidney Disease Patients - Kumaresan Ramanathan, Giri Padmanabhan (Journal of Applied Pharmaceutical Science, 2015)
Secondary hyperparathyroidism is common in patients with chronic kidney disease (CKD). Currently, cinacalcet has evidently improved the management of secondary hyperparathyroidism in patients on hemodialysis. Though, to the best of our knowledge, there are no studies addressing the dose regimen of cinacalcet in CKD stage II to IV. Hence we decided to study and evaluate the efficacy of cinacalcet in the treatment of secondary hyperparathyroidism in two different dose schedules. A total of 174 patients (M: 138, F: 36), ages ranging from 23 to 87 years with CKD stage II –IV not on dialysis and intact PTH (iPTH) >150 pg/dl were enrolled in this study. The study population was divided into two groups. Group I: daily 30 mg cinacalcet hydrochloride and Group II: weekly twice 30 mg cinacalcet hydrochloride. Both groups received cinacalcet hydrochloride 30 mg with the main meal. In group I, 42 patients (48 %) stopped the drug within one month due to various side effects. During the follow up, the levels of iPTH decreased significantly in both the groups within a period of four weeks & persisted till the end of the study. No significant side effects requiring stoppage of the drug were noted in the group II study population. In conclusion, cinacalcet hydrochloride 30 mg twice weekly is a safe regimen in suppressing high PTH levels in CKD patients.
Keywords: Secondary hyperpathyroidism, cinacalcet hydrochloride, Chronic kidney disease, parathyroid hormone.